Supporting Effective Transitions From University to Post-graduation for Autistic Students - Lucas, Rebecca; Cage, Eilidh; James, Alana I. (Frontiers in Psychology, 2022)
Background: The number of autistic students graduating is increasing, however little is known regarding their transition out of university. Understanding this transition is particularly pertinent with regards to the employment of autistic graduates. It is vital that we understand autistic people’s experiences of the transition and identify what support would be beneficial during this time. Method: Thirty-four autistic graduates from the UK took part in a mixed methods study exploring their transition experience. Both quantitative and qualitative questions were used to obtain in-depth information concerning participants’ experiences. Participants completed questions regarding their experiences and emotions in relation to the transition, the support they received for the transition and their career and post-graduation plans. Results: Participants reported high levels of fear and low preparedness for the transition. They did not feel well supported in preparing for the transition or for their future career. In the six months pre-graduation, 59% of participants had accessed emotion-related transition support and 70% accessed career-related support. Post-graduation, one-third accessed emotion-related or career-related support. Perspectives on this accessed support were mixed, as were transition experiences. Additional support desired included preparation for life changes, career planning, employment accessibility, and autism-specific support. Advice for future students centred on forward planning. Conclusions: These results highlight the importance of supporting autistic students with the transition out of university. Service provision should be tailored to autistic students’ needs and support early planning for the transition.